Antibiotic use among hospitalized children with lower respiratory tract infections: a multicenter, retrospective study from Punjab, Pakistan. Issue 1 (2nd January 2022) - Mustafa, Zia Ul; Salman, Muhammad; Aslam, Naeem; Asif, Noman; Hussain, Khalid; Shehzadi, Naureen; Hayat, Khezar
ABSTRACT: Background: Lower respiratory tract infection (LRTI) is one of the triggering factors toward death in children below the age of five years necessitating appropriate antibiotic selection. This study aimed to evaluate antibiotic use among hospitalized children (≤5 years age) with LRTIs. Methods: A retrospective study was conducted in seven health facilities of the central region of Punjab province of Pakistan. The medical records of hospitalized children ≤5 years diagnosed with LRTI were thoroughly evaluated to get information on demographics, clinical characteristics, and details of prescribed antibiotics. The appropriateness of antibiotics was assessed according to guidelines of the British National Formulary due to a lack of indigenous standard treatment guidelines. Results: The medical records of 5926 children were searched with the majority (70.9%) diagnosed with community-acquired pneumonia (CAP) followed by acute bronchitis (14.1%). Ceftriaxone plus ampicillin and ceftriaxone plus ampicillin plus amikacin were prescribed to 39% and 11.7% study population, respectively. One-fourth of children were prescribed the wrong dose, and more than half were encountered with the incorrect route of antibiotic administration. Alarmingly, 90.2% of antibiotic prescriptions were inappropriate in our findings. Conclusions: Current surveillance study revealed a worrying degree of antibiotic misuse among hospitalized LRTI children aged ≤5 years.